2017
DOI: 10.1007/s11540-018-9357-4
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Variable Rate Technology Application in Potato in The Netherlands

Abstract: Precision agriculture is a farming management concept based on observing, measuring and responding to inter- and intra-field variability in crops. In this paper, we focus on responding to intra-field variability in potato crops and analyse variable rate applications (VRAs). We made an overview of potential VRAs in potato crop management in The Netherlands. We identified 13 potential VRAs in potato, ranging from soil tillage to planting to crop care to selective harvest. We ranked them on availability of ‘proof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 9 publications
1
23
0
Order By: Relevance
“…This allows us to control weeds more efficiently and reduce environmental risks, as there are no applications of underdoses or overdoses. This technology works by integrating a variable rate control system with the sprayer for herbicide application [8,9].…”
Section: Variable Rate Application (Vra) Of Herbicidesmentioning
confidence: 99%
“…This allows us to control weeds more efficiently and reduce environmental risks, as there are no applications of underdoses or overdoses. This technology works by integrating a variable rate control system with the sprayer for herbicide application [8,9].…”
Section: Variable Rate Application (Vra) Of Herbicidesmentioning
confidence: 99%
“…The technology can reduce material and labor costs, maximize productivity, and decrease the impact that over-application may have on the environment. A case regarding tomato production in the Netherlands showed that about 25% of pesticides and nitrogen-fertilizer use can be saved with the adoption of VRTs (Kempenaar et al, 2017). While traditionally used in large-scale industrialized farms, VRT could also be adopted in peri-urban farms.…”
Section: Water Technologies For Few Nexus Systemsmentioning
confidence: 99%
“…This information assists in the planning of sustainable managements using specific measures that bring benefits such as higher economic return and lower environmental impact (ROCHA et al, 2015). Several studies present economy of up to 25% for the application of pesticides when using the precision agriculture technique termed variable-rate application, i.e., when the input is applied based on the spatial arrangement of the target (GUNDY; DILLE; ASEBEDO, 2017;KEMPENAAR et al, 2017;BHAKTA;PHADIKAR;MAJUNDER, 2019).…”
Section: Introductionmentioning
confidence: 99%